Carotid Body Type-I Cells Under Chronic Sustained Hypoxia: Focus on Metabolism and Membrane Excitability - Pulgar-Sepúlveda, Raúl; Varas, Rodrigo; Iturriaga, Rodrigo; Del Rio, Rodrigo; Ortiz, Fernando C. (Frontiers in Physiology, 2018)
Chronic sustained hypoxia (CSH) evokes ventilatory acclimatization characterized by a progressive hyperventilation due to a potentiation of the carotid body (CB) chemosensory response to hypoxia. The transduction of the hypoxic stimulus in the CB begins with the inhibition of K+ currents in the chemosensory (type-I) cells, which in turn leads to membrane depolarization, Ca2+ entry and the subsequent release of one- or more-excitatory neurotransmitters. Several studies have shown that CSH modifies both the level of transmitters and chemoreceptor cell metabolism within the CB. Most of these studies have been focused on the role played by such putative transmitters and modulators of CB chemoreception, but less is known about the effect of CSH on metabolism and membrane excitability of type-I cells. In this mini-review, we will examine the effects of CSH on the ion channels activity and excitability of type-I cell, with a particular focus on the effects of CSH on the TASK-like background K+ channel. We propose that changes on TASK-like channel activity induced by CSH may contribute to explain the potentiation of CB chemosensory activity.